Motivation of Farmers in Processing Waste of Cattle Become Composite Fertilizer in Community of Simantri Farmer in Gianyar District - S. V., Devi Dasy; Tatik Inggriati, N W.; Suarta, G. (Jurnal Peternakan Tropika, 2019)
This study aims to 1). To find out the motivation of simantri member farmers in processing cow manure into compost, 2). To find out the factors that influence the motivation of farmers Simantri members in making compost from cow manure. 3). To find out the purpose of making compost in agricultural business carried out by farmers of Simantri members in Gianyar Regency. This research was conducted in Kelusa Village, Payangan Subdistrict and Keliki Village, Tegallalang District, Gianyar Regency, from December to February 2019. This research was selected using the Purposive Sampling method. Respondents were 41 census farmers in the census group. The analysis used was qualitative descriptive analysis and Spearman's level correlation test. The results of this study indicate that the motivation of farmers in simantri Bhuana Kerti and Dwi Merta Sari members is included in the strong category. Factors such as age, formal education, non-formal education, number of livestock raised, waste treatment goals, knowledge of waste management, have a significant relationship (p<0.05) while the experience of raising cattle and the number of dependents have a relationship that is (p> 0.05) with motivation level. Based on the results of the study it can be concluded that, 1). motivation of simantri member farmers in processing cow manure into compost including strong categories, 2). Factors related to motivation are age, formal education, non-formal education, number of livestock kept, waste treatment goals, processing knowledge waste, experience of raising cattle and number of family dependents, 3). The purpose of making compost is to increase income. Keywords: Motivation, waste, livestock, cattle, compost